Illicit drug trafficking in Indonesia from the perspective of asymmetric warfare - Beny Abukhaer Tatara; Suhirwan Suhirwan; Mochammad Afifuddin (Trigin Publisher, 2022)
The dynamics of the international strategic environment were influenced by the dynamics of international politics and security which require countries in the world to protect their national interests from a spectrum of threats, both actual and potential, which were increasingly complex and have implications for national defense, one of which was the illicit drug traficking. In several countries, drug trafficking was categorized as part of asymmetric warfare. This research aimed to analyze the illicit drugs trafficking drugs in Indonesia from the perspective of asymmetric warfare. This study used a qualitative method with a literature study approach. The resulted of the study show that the illicit drug trafficking in Indonesia fell into the category of asymmetric warfare that happen between state actors against non-state actors (drug dealers) or vice versa. Drug dealers, especially big dealers, armed themselves with firearms to fight against law enforcement officers. There was an illicit drug traficking in Indonesia that has linkage with terrorists, especially for funding their act. The impact of illicit drug trafficking included demographic, economic, socio-cultural and defense and security aspects.